Personalized Hand Modeling from Multiple Postures with Multi‐View Color Images. (24th November 2020) - Wang, Yangang; Rao, Ruting; Zou, Changqing
Abstract: Personalized hand models can be utilized to synthesize high quality hand datasets, provide more possible training data for deep learning and improve the accuracy of hand pose estimation. In recent years, parameterized hand models, e.g., MANO, are widely used for obtaining personalized hand models. However, due to the low resolution of existing parameterized hand models, it is still hard to obtain high‐fidelity personalized hand models. In this paper, we propose a new method to estimate personalized hand models from multiple hand postures with multi‐view color images. The personalized hand model is represented by a personalized neutral hand, and multiple hand postures. We propose a novel optimization strategy to estimate the neutral hand from multiple hand postures. To demonstrate the performance of our method, we have built a multi‐view system and captured more than 35 people, and each of them has 30 hand postures. We hope the estimated hand models can boost the research of high‐fidelity parameterized hand modeling in the future. All the hand models are publicly available on www.yangangwang.com .